2000
DOI: 10.1074/jbc.m001500200
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Esters and Cytokines Regulate the Expression of theNEMO-related Protein, a Molecule Involved in a NF-κB-independent Pathway

Abstract: The NF-B signaling pathway plays a crucial role in the immune, inflammatory, and apoptotic responses. Recently, we identified the NF-B Essential Modulator (NEMO) as an essential component of this pathway. NEMO is a structural and regulatory subunit of the high molecular kinase complex (IKK) responsible for the phosphorylation of NF-B inhibitors. Data base searching led to the isolation of a cDNA encoding a protein we called NRP (NEMO-related protein), which shows a strong homology to NEMO. Here we show that NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 34 publications
4
133
1
Order By: Relevance
“…Rab8 is linked to huntingtin by FIP-2, and the expression of FIP-2/NEMO-related protein is regulated by cytokines and phorbol esters (Hattula and Peränen, 2000;Schwamborn et al, 2000). Because phorbol esters activate PKC and modulate actin assembly, we determined their effects on Rab8 and Rabin8's distributions.…”
Section: Activation Of Pkc Results In Polarized Distribution Of Rabinmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab8 is linked to huntingtin by FIP-2, and the expression of FIP-2/NEMO-related protein is regulated by cytokines and phorbol esters (Hattula and Peränen, 2000;Schwamborn et al, 2000). Because phorbol esters activate PKC and modulate actin assembly, we determined their effects on Rab8 and Rabin8's distributions.…”
Section: Activation Of Pkc Results In Polarized Distribution Of Rabinmentioning
confidence: 99%
“…Rab8 is known to interact with the germinal center kinase, a protein involved in TNF-alpha signaling (Ren et al, 1996). There is also a connection of the Rab8-interacting protein optineurin (FIP-2) to TNF-alpha-mediated signals (Li et al, 1998;Schwamborn et al, 2000). TNF-alpha is a major mediator of inflammatory responses, and it induces changes in several cellular processes, such as cell migration, differenti- Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…the IKK␥-related coiled-coil protein NRP (NEMO-related protein) is a Golgi-resident protein, although its function in signaling is currently unknown (39). We are currently trying to determine whether NRP plays any role in IKK relocalization to the Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…As for NEMO, Optn is detected in a high molecular complex, probably in association with other interacting proteins. 5 Optn is ubiquitous, and its expression can be induced by TNFα and interferons, probably as a result of NFκB activation, since Optn possesses a functional NFκB binding site in its promoter. 1,5,6 Despite its homology with NEMO, numerous studies indicate that Optn is involved in multiple fundamental cellular functions, signaling pathways and host defense mechanisms that are not related to NFκB.…”
Section: Toward An Integrative View Of Optineurin Functionsmentioning
confidence: 99%
“…3 Optn exhibits strong homology with the NEMO (NFκB essential modulator) at both the primary sequence and domain organization levels. 5 Sequence alignment of the two proteins revealed that Optn shares 53% similarity with NEMO except for the presence of an "insert" of 166 amino acids located in the N-terminal region and containing a putative leucine zipper (LZ) (Fig. 1).…”
mentioning
confidence: 99%